Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan: Studi Kasus RSUD Dr. Wahidn Sudiro Husodo Kota Mojokerto - Mitha Hapsari, Febriyanie (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The purpose of this research is to determine the effect of work motivation on employee performance, the effect of work discipline on employee performance, the effect of the work environment on employee performance at RSU Dr. Wahidin Sudiro Husodo, Mojokerto City. In this study using multiple linear regression analysis technique with a quantitative approach method. The number of population used in this study was 353 employees with proportional random sampling method so that the sample in this study was 76 employees. The results of the research collected were obtained from the distribution of questionnaires and were further analyzed using SPSS For Windows. The results of the study found that: (1) Work motivation has a t value of 5,093 with a significance probability level of 0.000 so that it is known that tcount > ttable (5,093 > 1.66571) and a significance level of 0.000 < 0.05. Which means Work Motivation (X1) has a significant effect in a positive direction on employee performance at RSU Dr. Wahidin Sudiro Husodo. (2) Work discipline has a t count value of 2.166 with a significance probability level of 0.032 so that it is known that tcount > ttable (2.166 > 1.66571) and a significance level of 0.032 < 0.05. Which means that Work Discipline (X2) has a significant effect in a positive direction on the performance of employees at RSU Dr. Wahidin Sudiro Husodo. (3) The work environment has a t-count value of 2.144 with a significance probability level of 0.034 so that it is known that tcount > ttable (2.144 > 1.66571) and a significance level of 0.034 < 0.05. Which means that the Work Environment (X3) has a significant effect with the direction positive on employee performance at RSU Dr. Wahidin Sudiro Husodo.